Production and N-glycan engineering of Varlilumab in Nicotiana benthamiana - Nguyen, Kim Dua; Kajiura, Hiroyuki; Kamiya, Ryo; Yoshida, Takahiro; Misaki, Ryo; Fujiyama, Kazuhito (Frontiers in Plant Science, 2023)
N-glycan engineering has dramatically evolved for the development and quality control of recombinant antibodies. Fc region of IgG contains two N-glycans whose galactose terminals on Fc-glycan have been shown to increase the stability of CH2 domain and improve effector functions. Nicotiana benthamiana has become one of the most attractive production systems for therapeutic antibodies. In this study, Varlilumab, a CD27-targeting monoclonal antibody, was transiently produced in fresh leaves of soilgrown and hydroponic-grown N. benthamiana, resulted in the yield of 174 and 618 µg/gram, respectively. However, the IgG produced in wild-type N. benthamiana lacked the terminal galactose residues in its N-glycan. Therefore, N-glycan engineering was applied to fine-tune recombinant antibodies produced in plant platforms. We further co-expressed IgG together with murine β1,4galactosyltransferase (GALT) to modify plant N-glycan with β1,4-linked Gal residue(s) and Arabidopsis thaliana β1,3-galactosylatransferase (β1,3-GALT) to improve galactosylation. The coexpression of IgG with each of GALTs successfully resulted in modification of N-glycan structures on the plant-produced IgG. Notably, IgG co-expressed with murine β1,4-GALT in soil-grown N. benthamiana had 42.5% of N-glycans variants having galactose (Gal) residues at the non-reducing terminus and 55.3% of that in hydroponic-grown N. benthamiana plants. Concomitantly, N-glycan profile analysis of IgG co-expressed with β1,3-GALT demonstrated that there was an increased efficiency of galactosylation and an enhancement in the formation of Lewis a structure in plant-derived antibodies. Taken together, our findings show that the first plant-derived Varlilumab was successfully produced with biantennary β1,4-galactosylated N-glycan structures.